Brassinosteroids: A Promising Option in Deciphering Remedial Strategies for Abiotic Stress Tolerance in Rice - Sharma, Isha; Kaur, Navdeep; Pati, Pratap K. (Frontiers in Plant Science, 2017)
Rice is an important staple crop as it feeds about a half of the earth’s population. It is known to be sensitive to a range of abiotic stresses which result in significant declines in crop productivity. Recently, the use of phytohormones for abiotic stress amelioration has generated considerable interest. Plants adapt to various environmental stresses by undergoing series of changes at physiological- and molecular-levels which are cooperatively modulated by various phytohormones. Brassinosteroids (BRs) are a class of naturally occurring steroidal phytohormones, best known for their role in plant growth and development. For the past two decades, greater emphasis on studies related to BRs biosynthesis, distribution and signaling has resulted in better understanding of BR function. Recent advances in the use of contemporary genetic, biochemical and proteomic tools, with a vast array of accessible biological resources has led to an extensive exploration of the key regulatory components in BR signaling networks, thus making it one of the most well-studied hormonal pathways in plants. The present review highlights the advancements of knowledge in BR research and links it with its growing potential in abiotic stress management for important crop like rice.